Factors Influencing Unemployment Rate: A Comparison Among Five Asean Countries - Aljileedi Mustafa Rayhan, Amyir; Rusdarti, Rusdarti; Yanto, Heri (Universitas Negeri Semarang, 2020)
Unemployment can occur due to imbalances in the labor market. This shows that the number of labor forces offered exceeds the number of labor forces requested. The purpose of the study is to analyze factors influencing the unemployment rate: a comparison among five ASEAN countries. This study used quantitative research. The data collection method in this study is documentation with secondary data since the year 2000-2018. The hypothesis test in this study is done by using Regression analysis and ANOVA with single Classification followed by Post Hoc Analysis. Analysis results analyze factors influencing the unemployment rate: a comparison among ASEAN-5 countries is showed (F=4.599; p<0.002). There is a significant impact of wage, inflation, economic growth and education on unemployment in ASEAN countries. The result found that among the several factors that cause unemployment in a countries the most significant is inflation value is 0.003 < 0.05. While other factors such as wage, economic growth, and education affect but are not significant. Future research should add other variables affecting the unemployment rate.